PENYULUHAN KESEHATAN DAN PEMERIKSAAN FISIK, TEKANAN DARAH, GULA DARAH, DAN ASAM URAT RW 15 DESA SINDANGGALIH KARANGAPAWITAN KABUPATEN GARUT - Andhika Lungguh Perceka; N. Ai Erlinawati; Hasbi Taobah Ramdani; Herlin Rusyani; Aceng Ali Awaludin (LP4M STIKes Karsa Husada Garut, 2022)
Health is a human right and an investment for the success of nation building. For this reason, it is necessary to carry out comprehensive health development in order to realize a healthy society. The purpose of this activity is to provide initial health information to the public about physical examinations, and to provide counseling based on the results of health examinations so that the realization of a healthy society. The service technique is carried out using lecture and question and answer techniques as well as checking blood pressure, cholesterol, uric acid and checking blood sugar. The participants who took part in this activity were 40 people. From this activity, it was concluded that the knowledge of the residents before the health education activities was 60% or 30 residents did not know about hypertension, diabetes and gout after the counseling was carried out increased by 90% knowing/understanding blood pressure and other similar activities carried out regularly routine.